Teachers' Perceptions of Sustainable Development Goals (SDGB) Based Education to Increase Students' Social Awareness Through Social Studies Learning in Elementary Schools - Afandi, Muhamad; Rachmadtullah, Reza (Journal of Innovation and Research in Primary Education, 2025)
This study intends to determine teachers' perceptions of Sustainable Development Goals (SDGs)-based education to improve students' social awareness through social studies learning in elementary schools. The method employed was a qualitative approach with a case study design. The data were gathered through in-depth interviews and non-participant observations of five elementary school teachers with more than five years of teaching experience. The findings uncovered that teachers' understanding of the SDGs varied, with some teachers taking more initiative in integrating SDG values ​​into their learning. In contrast, others encountered difficulties due to limited training and resources. The strategies implemented encompassed classroom discussions and community-based projects as well as the utilization of technology, such as documentary videos and news articles. Nonetheless, the primary challenges were limited time and access to in-depth teaching materials. The impact of SDGs-based education on students was observed in their increased understanding of global issues, such as climate change and social inequality. Students also exhibited greater interest in social and environmental activities. However, the impact differed depending on the intensity of SDGs implementation in learning. In conclusion, although the implementation of SDGs in elementary schools can increase students' social awareness, further support from the government and schools is required, including teacher training and the provision of adequate resources to strengthen the integration of SDGs in the curriculum.